Factors influencing platelet isolation: a prospective multicenter study from Western China. (31st December 2023) - Liu, Shan; Yang, Guishu; Zeng, Guangqun; Zhou, Xihao; Chen, Rong; Chen, Bin; Chen, Jin; Wen, Xiaoxia; Zhang, Xingmei; Ren, Hanxiao; Zu, Ruiling; Wang, Dongsheng; et al.
Abstract: Tumor-educated platelets (TEPs) have been widely reported to have promising application potential; nonetheless, platelet isolation from peripheral blood is an important but neglected step in TEPs research for platelet-based liquid biopsy. In this article, we discussed some common influence factors for platelet isolation. To investigate the factors involved in platelet isolation, a prospective multicenter study was conducted on healthy Han Chinese adults (18 to 79 years of age). A total of 208 individuals were included in the final statistical analysis out of the 226 healthy volunteers who were prospectively enrolled from four hospitals. The primary study metric was the platelet recovery rate (PRR). The similar pattern was observed in the four hospitals, The PRR at room temperature (23°C±2°C) was slightly higher than the PRR at cold temperature (4°C±2°C). Moreover, the PRR gradually decreased as the storage time increased. The PRR for samples within 2 hours of storage is significantly higher than for samples beyond 2 hours ( p  < .05). Additionally, PRR was also affected by the equipment used in different centers. This study confirmed several factors that influence platelet isolation. In our study, we indicated that platelet isolation should be performed within two hours of peripheral blood draw and held at room temperature until isolation, and that centrifuge models should be fixed during the extraction process, which will further improve the research progress of platelet-based liquid biopsy in cancer. Plain Language Summary: What is the context? Globally, cancer is one of the leading cause of premature death. Early screening is important for cancer diagnosis and treatment and can even significantly lower cancer mortality Globally, cancer is one of the leading cause of premature death. Early screening is important for cancer diagnosis and treatment and can even significantly lower cancer mortality For the liquid biopsy, isolation is an important step. Early studies have explored the influencing factors of exosome, circulating tumor cells (CTCs), and other components extraction in liquid biopsy. Despite platelet also being an excellent source of liquid biopsy, few studies have explored the factors that influence platelet isolation.Considering the importance of platelet isolation in tumor-based platelet liquid biopsy, our aim is to optimize platelet isolation conditions as much as possible to obtain a high platelet recovery rate. What is new? In this study, we conducted a prospective multicenter study ofhealthy adults from four centers, combining whole blood with platelet-richplasma to investigate factors influencing platelet recovery rate (PRR) during platelet isolation. In our study, we indicated that platelet isolation should be performed within two hours at room temperature, and that centrifuge models should be fixed during the extraction process, which will further improve the research progress of platelet-based liquid biopsy in cancer. What is the impact? In future platelet-related studies, we should fix the sample storage temperature, storage time and centrifuge model in the process of platelet extraction, so as to reduce the variables affecting platelet extraction as much as possible and ensure the stable recovery rate of platelet extraction.